2016
DOI: 10.1001/jamasurg.2016.1137
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Modified FOLFIRINOX Treatment Followed by Capecitabine-Based Chemoradiation for Borderline Resectable Pancreatic Cancer

Abstract: IMPORTANCE Although consensus statements support the preoperative treatment of borderline resectable pancreatic cancer, no prospective, quality-controlled, multicenter studies of this strategy have been conducted. Existing studies are retrospective and confounded by heterogeneity in patients studied, therapeutic algorithms used, and outcomes reported. OBJECTIVE To determine the feasibility of conducting studies of multimodality therapy for borderline resectable pancreatic cancer in the cooperative group sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
294
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 402 publications
(305 citation statements)
references
References 29 publications
5
294
4
2
Order By: Relevance
“…Several trials have shown that preoperative treatment of borderline resectable pancreatic adenocarcinoma can be effective and well-tolerat-ed. [148][149][150][151][152][153][154][155] Neoadjuvant therapy should preferably be administered at or coordinated through a high-volume center. Upfront resection in patients with borderline resectable disease is no longer recommended, as of the 2016 version of these guidelines.…”
mentioning
confidence: 99%
“…Several trials have shown that preoperative treatment of borderline resectable pancreatic adenocarcinoma can be effective and well-tolerat-ed. [148][149][150][151][152][153][154][155] Neoadjuvant therapy should preferably be administered at or coordinated through a high-volume center. Upfront resection in patients with borderline resectable disease is no longer recommended, as of the 2016 version of these guidelines.…”
mentioning
confidence: 99%
“…Recently, Katz et al concluded a trial and showed that 68% of patients with borderline pancreatic cancer who underwent therapy with modified FOLFIRINOX regimen followed by capecitabine-based chemoradiation underwent successful surgical resection. The median survival for these patients were 21.7 months (95% CI 15.7 to not reached) 12. Similarly, Rombouts et al reported pCR in 7% of resected specimen after the patients were initially diagnosed with locally advanced pancreatic cancer and underwent therapy with either FOLFIRINOX alone, modified FOLFIRINOX or in combination with radiation therapy 13…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the technical conduct of surgery, including the extent of vascular dissection and lymphadenectomy, was mandated by protocol. These design elements are critical to the interpretation of investigations of preoperative therapy for pancreatic cancer, particularly in the multi-institutional setting [6, 7]. …”
mentioning
confidence: 99%